Penguatan Literasi Numerasi Anak-Anak di Desa Sembalun Lawang melalui Pengenalan Metode Jarimatika - Muhammad Alwan; Husairi Husairi; Muhammad munir; Hayaturraiyan; Nita Sunarya Herawati (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Number operations is a fundamental and very important material in mathematics learning. However, conditions in the field show that many children still have a low understanding of the concept of jarimatik. This is due to children's lack of interest in mathematics from an early age because it is considered a difficult subject, so their interest in learning becomes low. To overcome this, it is necessary to implement simple and fun learning methods so that children are interested in learning mathematics from an early age. This service activity uses a mentoring method in the form of tutoring which is carried out regularly by children in Sembalun Lawang Village, Sembalun District. every Saturday and Sunday for one month. The goal of this activity is to help children understand the concept of number operations in an easy way while increasing their interest in learning through a fun approach. The service method used is Participatory Action Research (PAR), with coordination and socialization steps, the implementation of tutoring, observation and data collection, and reflection. The results of this activity showed an increase in students' numeracy skills in addition, subtraction, multiplication, and division operations, as well as an increase in interest in learning mathematics among children in Sembalun Lawang Village, Sembalun District through the application of the jarimatika method in tutoring.